The bodily divined icons and the lustful functions in "Beginnings of the body, Ends of the sea" by "Adonis". - برهم لطفيّة إبراهيم; مصطفى محمد حسن (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
"Beginnings of the body, Ends of the sea" overflows of different bodily icons of multi- cultural meanings expressing the relation between masculinity and femininity patterns .Furthermore, these icons unload the cultural implications ,which overriding the lustful aims into horizons digging culturally in the masculine paradigm ,which links the concept of body to sex and lust and finally, to deconstruct the intellect of seeing body mere organs breeding or entangling. Research concludes that lust is not a necessary in the feminine pattern as such as the masculine one, which unload the burden of patriarchal authority by adhering sex. On the other hand, the divinity of bodily organs cannot be without the masculinity acknowledgement that femininity is the biological basis, especially legends tend to feminize the masculinity so that, there is no existence without female and there is no male without existence protecting and fertilizing by femininity.